2013
DOI: 10.1590/s0100-69912013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento de curto prazo com liraglutide no reganho de peso após cirurgia bariátrica

Abstract: ABSTRACT ABSTRACT ABSTRACTObjective Objective Objective Objective Objective: To evaluate the results of the use of Liraglutide in a group of patients undergoing surgical treatment of morbid obesity with unsatisfactory weight loss or regain of more than 15% of minimum reached weight. Methods Methods Methods Methods Methods: The authors conducted a retrospective analysis of 15 operated patients who had excess weight loss <50% after two years of follow-up or regained weight more than 15% of the minimum reached we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 13 publications
4
23
0
2
Order By: Relevance
“…The mean of this added weight loss was −7.6% (17.8 lbs) of total postsurgical weight. After further stratification, we found that patients who were prescribed medication at weight plateau lost a similar amount of weight compared to those who were prescribed medication after weight regain, (− 6.9% or 16.1 lbs and − 7.7% or 18.2 lbs) consistent with findings reported in previous literature [27,28,32,33]. Consequently, total weight loss percentage from preoperative status was higher in patients who were prescribed medications at their plateau than in those patients who were prescribed medication after weight regain had occurred (32.3% versus 26.8%; P = .486).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The mean of this added weight loss was −7.6% (17.8 lbs) of total postsurgical weight. After further stratification, we found that patients who were prescribed medication at weight plateau lost a similar amount of weight compared to those who were prescribed medication after weight regain, (− 6.9% or 16.1 lbs and − 7.7% or 18.2 lbs) consistent with findings reported in previous literature [27,28,32,33]. Consequently, total weight loss percentage from preoperative status was higher in patients who were prescribed medications at their plateau than in those patients who were prescribed medication after weight regain had occurred (32.3% versus 26.8%; P = .486).…”
Section: Discussionsupporting
confidence: 89%
“…While revisional bariatric surgery has been employed in this patient population [21], these often fail, require reoperation, and are associated with complications [2224]. Endoscopic pouch plications, stoma reductions, and sclerotherapy have been utilized to treat inadequate weight loss and weight regain in bariatric surgery patients [25,26], but this too has proven ineffective long term [27,28]. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective review demonstrated that phentermine alone and a phentermine-topiramate combination, in addition to diet and exercise, appear to be viable options for weight loss in RYGB and adjustable gastric banding patients who experienced weight recidivism or weight loss plateau [160]. Another study showed that medical treatment directed to the control of satiety using liraglutide may be an alternative treatment of patients with poor weight loss or weight regain after surgery [161]. Since most of the studies reporting the utility of anti-obesity drugs are retrospective and such clinical studies at present are of small scale, further prospective randomised clinical trials should be performed to demonstrate the effect of drugs on prevention and treatment of weight regain.…”
Section: Weight Regain Prevention and Managementmentioning
confidence: 99%
“…Recently, some cardiovascular safety trials with diabetes medications have demonstrated that these drugs offer cardiovascular protection (2); more data on hard outcomes are required to better assess not only the efficacy, but mainly the safety in very large series before endorsing the widespread indication of bariatric surgery in the subpopulation of type 2 diabetics with a BMI below 35 kg/m 2 . A significant proportion of individuals undergoing bariatric surgery experiment weight regain, residual diabetes or diabetes relapse (i.e., around one third of initial remitters over five years do not achieve remission or have diabetes recurrence), requiring to cope with the residual diabetes and emerging obesity (2,3) and also to deal with lifelong nutritional deficiencies and other potential long-term complications, such as vomiting, adhesions, strictures, gallstones, hernias, drinking problems, and small-bowel obstruction (4,5). In the scope under discussion, it is essential that the diagnosis of diabetes in patients undergoing bariatric surgery be reliable and safe.…”
mentioning
confidence: 99%